Harmoni Hak Dan Kewajiban Negara Serta Warga Negara Dalam Demokrasi Indonesia Berdasarkan Kedaulatan Rakyat Dan Musyawarah Untuk Mufakat - Eli Sabrifha (CV. SINAR HOWUHOWU, 2026)
This study discusses the harmony between the rights and obligations of the state and citizens within the Indonesian democratic system, which is based on popular sovereignty and the principle of deliberation to reach consensus. Indonesian democracy places the people as the highest holders of power while emphasizing the balance between the fulfillment of rights and the implementation of obligations in national and state life. This research aims to analyze the relationship between rights and obligations as well as the role of deliberation and consensus in maintaining national unity and stability. The method used in this study is qualitative research with a descriptive approach through literature review from various legal sources and related references. The results show that harmony can be achieved when the state is able to protect the rights of citizens, while society actively carries out its obligations in democratic life. In addition, deliberation to reach consensus is a distinctive characteristic of Pancasila democracy because it prioritizes common interests over personal or group interests.